How do annoying environmental stimuli affect cognitive failures and sleep quality in intensive care unit nurses? Mediating role of mood - Godarzi, Zohre; Sadegh Sohrabi, Mohammad; Heidarimoghadam, Rashid; Doosti-Irani, Amin; Babamiri, Mohammad (Investigación y Educación en Enfermería, 2025)
Objective. To investigate the relationship between disturbing environmental stimuli with sleep quality and cognitive failures in intensive care unit nurses, taking into account the mediating role of mood. Methods. A cross-sectional study was done with the participation of 201 intensive care unit nurses who were selected by census method from public hospitals in western Iran. Questionnaires were used to collect data, including: pittsburgh sleep quality index (PSQI), occupational cognitive failure questionnaire (OCFQ), Brunel Mood Scale (BRUMS), environmental annoyance and perceived noise annoyance. Modeling was done with univariate linear regression and multivariate regression. Results. The results of the study revealed that 84.1% of the participants had poor sleep quality. 13.3% experience cognitive failures at a low level, 61.7% at an average level, and 7% experience cognitive failures at a high level. By examining the mediating role of mood, it was found a significant and negative relationship between positive mood and: annoying environmental stimuli and people's positive mood (p=0.004) and noise annoyance (p=0.002); another significant and negative relationship was also observed between noice annoyance and cognitive failures (p<0.001). Conclusion. Considering the mediating role of mood in the effect of environmental variables on cognitive failures and quality of sleep, it is recommended to use psychological interventions to adjust nurses' mood.